Implikasi KUHP Baru terhadap Status Anak dari Hubungan Kohabitasi di Indonesia serta Kewajiban Tenaga Kesehatan - Sabrina Nuraini Sari; Suriyani Mansyur; Nella Septyani Suade; Sitti Nariman Korompot; Amelia Agustina; Asep Sapsudin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The 2023 Indonesian Criminal Code reform introduces the criminalization of cohabitation under Article 412, raising concerns regarding its implications for the civil status of children and vital administrative procedures. Although cohabitation is criminalized as a complaint-based offense, the provision may lead to misinterpretation among healthcare providers and civil registry officers, particularly regarding the issuance of birth certificates. Employing a normative juridical method with statutory, conceptual, and case approaches, this study examines the interaction between Article 412 of the Criminal Code, the Marriage Law, Constitutional Court Decision No. 46/PUU-VIII/2010, the Population Administration Law, and the 2023 Health Law. The findings indicate that the criminalization of cohabitation does not alter the civil status or rights of children, which remain protected through recognition mechanisms and identity rights. However, regulatory gaps persist due to the absence of clear implementation guidelines, posing risks of administrative barriers. Regulatory harmonization and technical directives are therefore necessary to ensure that children’s rights remain fully protected regardless of their parents’ legal circumstances.